Managing overactive bladder. (4th May 2019) - Robinson, D.; Cardozo, L.
Abstract: Overactive bladder (OAB) is a common and distressing condition which is known to increase with age and has a significant effect on quality of life. Whilst OAB is a symptomatic diagnosis, many patients will require basic investigations prior to initiating the appropriate management. This article will review the initial clinical assessment and management of women complaining of OAB including conservative measures and drug therapy, and will also focus on the role of estrogen. In addition, the management of refractory OAB will also be discussed including more invasive strategies such as neuromodulation, Botulinum Toxin, and reconstructive surgery.